2015
DOI: 10.2152/jmi.62.199
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular injection of adiponectin regulates locomotor activity in rats

Abstract: Enhancing exercise motivation is the best way to prevent obesity and diabetes. In this study, we examined whether adiponectin affects locomotion activity in Wister and Spontaneously-Running Tokushima-Shikoku (SPORTS) rats using two types of behavioral assays: home cage and wheel running activity. SPORTS rats were established from an original line from Wister strain that had shown high level of wheel running activity in our laboratory. Injection of adiponectin into the lateral ventricle of Wister rats and SPORT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Even though human-derived APN has been successfully synthesized, it is hard to investigate its neuroprotective effects through intravenous injection, as its relatively large size prevents it from passing through the blood-brain barrier. Due to this setback, APN knockout mice, adenovirus-mediated supplementation of APN, and intracerebroventricular injection of APN have been the primary methods of previous research [17, 20, 21]. In the present study, we used a variant of APN peptide that was synthesized according to the APN amino acid sequence and has been shown to simulate APN function.…”
Section: Introductionmentioning
confidence: 99%
“…Even though human-derived APN has been successfully synthesized, it is hard to investigate its neuroprotective effects through intravenous injection, as its relatively large size prevents it from passing through the blood-brain barrier. Due to this setback, APN knockout mice, adenovirus-mediated supplementation of APN, and intracerebroventricular injection of APN have been the primary methods of previous research [17, 20, 21]. In the present study, we used a variant of APN peptide that was synthesized according to the APN amino acid sequence and has been shown to simulate APN function.…”
Section: Introductionmentioning
confidence: 99%
“…All these actions were dependent on AdipoR1, since inhibition of this receptor, and not of AdipoR2, completely reversed the effects described above. On the order hand, another previous study [3] using rats as animal model indicated other central effects of adiponectin on spontaneous activity, showing that these central effects might depend on the species since in our study the analyses were performed with Swiss mice. Additionally, in our study, there was no difference in the hypothalamic content of APPL2, a protein with a counter-regulatory effect on the insulin pathway [32].…”
Section: Discussionmentioning
confidence: 76%
“…The hypothalamus receives peripheral stimuli during the food intake and thermogenesis regulation [2]. Among these stimuli, we can highlight the action of adipokines and hormones (adiponectin and leptin) for adequate energy metabolism regulation [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations